Knockdown of TFIIS by RNA silencing inhibits cancer cell proliferation and induces apoptosis - Hubbard, Kyle (BioMed Central, 2008)
BACKGROUND: A common element among cancer cells is the presence of improperly controlled transcription. In these cells, the degree of specific activation of some genes is abnormal, and altering the aberrant transcription may therefore directly target cancer. TFIIS is a transcription elongation factor, which directly binds the transcription motor, RNA Polymerase II and allows it to read through various transcription arrest sites. We report on RNA interference of TFIIS, a transcription elongation factor, and its affect on proliferation of cancer cells in culture. METHODS: RNA interference was performed by transfecting siRNA to specifically knock down TFIIS expression in MCF7, MCF10A, PL45 and A549 cells. Levels of TFIIS expression were determined by the Quantigene method, and relative protein levels of TFIIS, c-myc and p53 were determined by C-ELISA. Induction of apoptosis was determined by an enzymatic Caspase 3/7 assay, as well as a non-enzymatic assay detecting cytoplasmic mono- and oligonucleosomes. A gene array analysis was conducted for effects of TFIIS siRNA on MCF7 and MCF10A cell lines. RESULTS: Knockdown of TFIIS reduced cancer cell proliferation in breast, lung and pancreatic cancer cell lines. More specifically, TFIIS knockdown in the MCF7 breast cancer cell line induced cancer cell death and increased c-myc and p53 expression whereas TFIIS knockdown in the non-cancerous breast cell line MCF10A was less affected. Differential effects of TFIIS knockdown in MCF7 and MCF10A cells included the estrogenic, c-myc and p53 pathways, as observed by C-ELISA and gene array, and were likely involved in MCF7 cell-death. CONCLUSION: Although transcription is a fundamental process, targeting select core transcription factors may provide for a new and potent avenue for cancer therapeutics. In the present study, knockdown of TFIIS inhibited cancer cell proliferation, suggesting that TFIIS could be studied as a potential cancer target within the transcription machinery.